Facile Construction of Hierarchical TiNb2O7/rGO Nanoflower With Robust Charge Storage Properties for Li Ion Batteries via an Esterification Reaction - Hu, Lei; Yang, Xulai; Chen, Yumeng; Wang, Lili; Li, Jiajia; Tang, Yujie; Zhang, Haitao (Frontiers in Energy Research, 2021)
TiNb2O7 (TNO) compound has been pursued tremendously due to its high theoretical capacity, high potential, and excellent cycle stability. Unfortunately, an intrinsic low electronic and ionic conductivity feature has restricted its broad applications in electrochemical energy storage fields. Two-dimensional (2D) nanostructures can effectively shorten Li-ion transport path and enhance charge transfer. Here, hierarchical structure TNO was constructed by using ethanol and acetic acid as particularly important organic chemicals of basic raw materials via a simple solvothermal reaction. Ethanol was found to play a critical role in the formation of 2D sheet structure. Meantime, reduced graphene oxide nanosheets can effectively improve electronic conductivity. As-obtained TiNb2O7 were wrapped further by graphene oxide nanosheets through a flocculation process. Their unique structure is beneficial to the final electrochemical performance. This study not only provides a general approach for the design of novel 2D nanomaterials wrapped by graphene because of the advantage of esterification reaction and flocculation reaction, but also improves the electronic and ionic conductivity simultaneously.